Pengaruh Dana Desa dan Tingkat Kemiskinan di Provinsi Lampung - Heru Wahyudi; Siti Nur Khotimah (Penerbit Goodwood, 2022)
Purpose: This research aims to analyze the effect of village funds, capital expenditures, unemployment, and education on poverty in regency in Lampung Province. Research methodology: This research uses panel data analysis method with Random Effect Model (REM). Results: The results showed that there was a negative and significant relationship between village funds on poverty, and there was a positive and significant relationship between the open unemployment rate on poverty. Meanwhile, mean years of schooling and capital expenditure variables have a negative and significant effect on poverty. Limitations: The limitation in this study is that the research area is still based on regency coverage, less specific if to analyze directly on the smallest coverage is the village. Contribution: This research is expected to be used as a consideration and reference in determining further development policies based on the data described in this study, especially in reducing poverty in Lampung Province.